Immune checkpoint inhibitor-associated risk for venous thromboembolism: a comprehensive analysis - Jean M Connors; F Stephen Hodi; Michael Manos; Anita Giobbie-Hurder; Tamara A Sussman; Nicole R LeBoeuf; Ian D Dryg; Jason L Weirather (Journal for ImmunoTherapy of Cancer)
Background The relationship between venous thromboembolism (VTE) and immune checkpoint inhibitor therapy (ICI) is unclear. This analysis investigates the incidence of and risk factors for VTE in VTE-naive patients with cancer receiving ICI treatment.Methods A retrospective cohort study of patients receiving any type or combination of ICI from 2009 to 2022 at Dana-Farber Cancer Institute was conducted to identify VTE occurring after initiation of ICI treatment. Cumulative incidences of VTE were determined using Fine and Gray’s methods. Associations between VTE, ICI regimens, and clinical risk factors were evaluated using propensity-score stratified, multivariable Cox proportional hazards models.Results In 10,638 patients without a prior history of VTE, the 6-month cumulative incidence of VTE was 7.6% (95% CI: 7.1% to 8.1%) and 11.1% (95% CI: 10.5% to 11.8%) at 12 months. Clinical risk factors included: age 15–59 (HR 1.27; 95% CI: 1.12 to 1.43; p=0.002), obesity (HR: 1.41; 95% CI: 1.16 to 1.71), and history of anticoagulation prior to ICI start (HR: 1.43; 95% CI: 1.26 to 1.61). Compared with pembrolizumab, treatment with ipilimumab/nivolumab increased the risk of VTE (HR: 1.36; 95% CI: 1.02 to 1.82), while durvalumab conveyed lower risk (HR: 0.52; 95% CI: 0.31 to 0.87). Treatment with programmed cell death ligand 1 had significantly reduced risk of VTE (HR: 0.79; 95% CI: 0.63 to 0.99) compared with programmed cell death 1 monotherapy. Dual ICI blockade with cytotoxic T lymphocyte antigen 4/PD-1 significantly increased the risk of VTE (HR: 1.43; 95% CI 1.12 to 1.84). Initiation of anticoagulation after starting ICI for indications other than VTE reduced the risk by 40% (HR: 0.60, 95% CI: 0.48 to 0.73).Conclusions ICI treatment appears to be independently associated with a high incidence of VTE in patients with cancer warranting further investigation.